Intraoperative arterial blood pressure lability is associated with improved 30 day survival - Levin, M.A.; Fischer, G.W.; Lin, H.-M.; McCormick, P.J.; Krol, M.; Reich, D.L. (British journal of anaesthesia : BJA, 2015)
Arterial blood pressure lability, defined as rapid changes in arterial blood pressure, occurs commonly during anaesthesia. It is believed that hypertensive patients exhibit more lability during surgery and that lability is associated with poorer outcomes. Neither association has been rigorously tested. We hypothesized that hypertensive patients have more blood pressure lability and that increased lability is associated with increased 30 day mortality. This was a retrospective single-centre study of surgical patients from July 2008 to December 2012. Intraoperative data were extracted from the electronic anaesthesia record. Lability was calculated as the modulus of the percentage change in mean arterial pressure between consecutive 5 min intervals. The number of episodes of lability >10% was tabulated. Multivariate logistic regression was performed to determine the association between lability and 30 day mortality using derivation and validation cohorts. Inclusion criteria were met by 52 919 subjects. Of the derivation cohort, 53% of subjects were hypertensive and 42% used an antihypertensive medication. The median number of episodes of lability >10% was 9 (interquartile range 5–14) per patient. Hypertensive subjects demonstrated more lability than normotensive patients, 10 (5–15) compared with 8 (5–12), P<0.0001. In subjects taking no antihypertensive medication, lability >10% was associated with decreased 30 day mortality, odds ratio (OR) per episode 0.95 [95% confidence interval (CI) 0.92–0.97], P<0.0001. This result was confirmed in the validation cohort, OR 0.96 (95% CI 0.93–0.99), P=0.01, and in hypertensive patients taking no antihypertensive medication, OR 0.96 (95% CI 0.93–0.99), P=0.002. Use of any antihypertensive medication class reduced this effect. Intraoperative arterial blood pressure lability occurs more often in hypertensive patients. Contrary to common belief, increased lability was associated with decreased 30 day mortality.